Mentoring perception, scientific collaboration and research performance: is there a 'gender gap' in academic medicine? An Academic Health Science Centre perspective. Issue 1092 (16th August 2016) - Athanasiou, Thanos; Patel, Vanash; Garas, George; Ashrafian, Hutan; Hull, Louise; Sevdalis, Nick; Harding, Sian; Darzi, Ara; Paroutis, Sotirios
Abstract: Objectives: The 'gender gap' in academic medicine remains significant and predominantly favours males. This study investigates gender disparities in research performance in an Academic Health Science Centre, while considering factors such as mentoring and scientific collaboration. Materials and methods: Professorial registry-based electronic survey (n=215) using bibliometric data, a mentoring perception survey and social network analysis. Survey outcomes were aggregated with measures of research performance (publications, citations and h-index) and measures of scientific collaboration (authorship position, centrality and social capital). Univariate and multivariate regression models were constructed to evaluate inter-relationships and identify gender differences. Results: One hundred and four professors responded (48% response rate). Males had a significantly higher number of previous publications than females (mean 131.07 (111.13) vs 79.60 (66.52), p=0.049). The distribution of mentoring survey scores between males and females was similar for the quality and frequency of shared core, mentor-specific and mentee-specific skills. In multivariate analysis including gender as a variable, the quality of managing the relationship, frequency of providing corrective feedback and frequency of building trust had a statistically significant positive influence on number of publications (all p<0.05). Conclusions: This is the first study in healthcare research to investigate the relationship between mentoring perception, scientific collaboration and research performance in the context of gender. It presents a series of initiatives that proved effective in marginalising the gender gap. These include the Athena Scientific Women's Academic Network charter, new recruitment and advertisement strategies, setting up a 'Research and Family Life' forum, establishing mentoring circles for women and projecting female role models.